Koen Lenaerts, Eugene Regan, Ulla Neergaard and Karsten Ensig Sørensen (eds), Shaping a Genuine Area of Freedom, Security and Justice (Hart 2024) - Loxa, Alezini ; 0000-0002-7345-6266 (Europarättslig tidskrift, 2025)
The Area of Freedom, Security and Justice (AFSJ), established by the Treaty of Lisbon under Article 3(2) TEU and regulated under Title V of the TFEU, is increasingly occupying a central place in the case law of the Court of Justice of the EU (CJEU). The former Vice-President of the Court, Judge Lars Bay Larsen, has played a key role in the development of the relevant case law, having acted as judge-rapporteur in a series of foundational cases for the interpretation of key concepts in the AFSJ. The purpose of the book under review is to honour his work, trace the development of case law in the area, and illustrate the function of the AFSJ as a driving force of EU law. Under the editorial direction of Koen Lenaerts, Eugene Regan, Ulla Neergaard, and Karsten Engsig Sørensen, a total of 36 authors with diverse academic and professional backgrounds, have come together to celebrate the work of Lars Bay Larsen and his contribution to the development of the AFSJ. The edited collection comprises 29 essays presented in four parts, which focus respectively on the framework, the driving principles, the dynamics, and the impact of the AFSJ. After a brief presentation of the contents of each of the four parts, the review will discuss the practical value as well as the constraints of this work.